Developing definitions for invasive fungal diseases in critically ill adult patients in intensive care units. Protocol of the FUNgal infections Definitions in ICU patients (FUNDICU) project. Issue 4 (22nd January 2019) - Bassetti, Matteo; Scudeller, Luigia; Giacobbe, Daniele R.; Lamoth, Frederic; Righi, Elda; Zuccaro, Valentina; Grecchi, Cecilia; Rebuffi, Chiara; Akova, Murat; Alastruey‐Izquierdo, Ana; Arikan‐Akdagli, Sevtap; Azoulay, Elie; et al.
Summary: Background: The reliability of diagnostic criteria for invasive fungal diseases (IFD) developed for severely immunocompromised patients is questionable in critically ill adult patients in intensive care units (ICU). Objectives: To develop a standard set of definitions for IFD in critically ill adult patients in ICU. Methods: Based on a systematic literature review, a list of potential definitions to be applied to ICU patients will be developed by the ESCMID Study Group for Infections in Critically Ill Patients (ESGCIP) and the ESCMID Fungal Infection Study Group (EFISG) chairpersons. The proposed definitions will be evaluated by a panel of 30 experts using the RAND/UCLA appropriateness methods. The panel will rank each of the proposed definitions on a 1‐9 scale trough a dedicated questionnaire, in two rounds: one remote and one face‐to‐face. Based on their median rank and the level of agreement across panel members, selected definitions will be organised in a main consensus document and in an executive summary. The executive summary will be made available online for public comments. Conclusions: The present consensus project will seek to provide standard definitions for IFD in critically ill adult patients in ICU, with the ultimate aims of improving their clinical outcome and facilitating the comparison and generalizability of research findings.